Melibatkan Partisipasi Mahasiswa untuk Meningkatkan Kualitas Proses Perkuliahan di Perguruan Tinggi - Andri Heryandi (Universitas Negeri Padang, 2022)
The quality of the lecturing process is an important part for higher education to obtain output in the form of quality graduates in accordance with the vision, mission, and goals of the higher education institution. One way this is done is by checking the suitability of the teaching process that has been carried out with a predetermined curriculum. Teaching suitability checks are usually carried out by matching the lecturing material that has been delivered by the teacher in a lecture, whether it is in accordance with the lecture syllabus. This can be biased when the teacher (as the entity that is assessed) has to enter the suitability of the lecturing data. Therefore, it is necessary for other parties who are also directly involved in the lecturing process to verify the lecturing process that has been entered by the teacher. This research is focused on making a quality monitoring system for the lecturing process that involves students as the party verifying the lecturing process. This verification process will use media in the form of email and electronic messages in the form of chat in the chat application. When a teacher enters the lecturing process data, which consists of the material presented and the students who are taking part in the lecture, a message to verify the lecturing process will be sent via email and chat to students. Students can verify whether the course is in accordance with the course syllabus plan. By checking the conformity charged to the learning participants, a better level of trust will be obtained in order to improve the quality of learning